EFFECTS OF THE ENTOMOPATHOGENIC FUNGUS BEAUVERIA BASSIANA ON HALYOMORPHA HALYS (Experimental biology, 2026)
Halyomorpha halys (brown marmorated stink bug) is an invasive polyphagous pest that causes significant economic damage to fruit, vegetable, and horticultural crops. The species' high reproductive capacity, broad range of host plants and adaptation to diverse climatic conditions have led to its rapid spread across many countries. The entomopathogenic fungus Beauveria bassiana is a promising biological pest control agent due to its high pathogenicity and environmental safety. The aim of this study was to evaluate the efficacy of a native isolate of B. bassiana against various stages of H. halys.Under laboratory conditions, eggs, nymphs, and adults were treated with conidial suspensions at concentrations of 1×10⁵–1×10⁸ conidia/ml. Mortality rates, infection dynamics, LT₅₀ and LT₉₀ values, and the sublethal effects of the fungus were studied. Results showed that mortality also increased with increasing conidia concentrations. The greatest effect was observed at a concentration of 1×10⁸ conidia/ml: nymph mortality reached 98%, adult mortality 95%, and egg mortality 74%. Furthermore, at the highest concentration, the LT₅₀ index was 3.7 days, indicating the high virulence of the local isolate. The fungus also reduced feeding activity, decreased movement intensity, and impaired reproductive performance. These results demonstrate that the local isolate of Beauveria bassiana exhibits high entomopathogenic activity against Halyomorpha halys and holds promise for use in integrated biological pest management programs.
Keywords: Halyomorpha halys, Beauveria bassiana, entomopathogenic fungi, biological control, invasive pest, mortality